Oxalylacetylenes as Dielectrophiles for Annulation of Quinoline Rings: Synthesis of Highly Functionalized 1,3-Oxazinoquinolines - Belyaeva, Kseniya V.; Nikitina, Lina P.; Gen’, Veronika S.; Afonin, Andrei V.; Trofimov, Boris A. (Synthesis, 2021)
Oxalylacetylenes act as dielectrophiles in the annulation of quinolines to give highly functionalized 1,3-oxazine cycles decorated with ethynyl, oxalyl, ester and aryl substituents. The annulation proceeds under mild conditions (room temperature, without catalyst) in 2:1 mode with respect to acetylene and quinoline to deliver 1,3-oxazinoquinolines in 45–88% yields. A beneficial feature of the reaction is that, in contrast to results on the reaction of quinolines with trifluoroacetylacetylenes in the presence of water, where H2O acted as a third electrophile, leading to the 1,3-oxazinoquinolines containing a hydroxyl group, this reaction well tolerates the aqueous medium. This reaction also tolerates isoquinoline and phenanthridine.
Keywords: alkynes; quinolines; oxazines; nucleophilic addition; annulation